2018
DOI: 10.1111/jmwh.12745
|View full text |Cite
|
Sign up to set email alerts
|

Interbirth Interval and Pregnancy Complications and Outcomes: Findings from the Pregnancy Risk Assessment Monitoring System

Abstract: The study's findings provide further support for encouraging women to space their pregnancies appropriately. Moreover, findings underscore the need to provide women with family planning services so that closely spaced pregnancies and unintended pregnancies can be avoided. Additional studies of the role of interbirth interval on these understudied pregnancy complications and outcomes are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…On the reverse, other studies indicated that there was a strong association between short IPI and PPROM [20]. Similarly, short IPI less than 18 months [21] increased the odds of the occurrence of PROM. Reduction of term PROM among women with optimal IPI in the current study can happen as a result of positive effect optimal IPI on Mom’s body.…”
Section: Discussionmentioning
confidence: 99%
“…On the reverse, other studies indicated that there was a strong association between short IPI and PPROM [20]. Similarly, short IPI less than 18 months [21] increased the odds of the occurrence of PROM. Reduction of term PROM among women with optimal IPI in the current study can happen as a result of positive effect optimal IPI on Mom’s body.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, articles were further excluded because of lack of risk estimates ( n = 89), having two or fewer birth spacing strata ( n = 80), birth spacing not measured ( n = 36), irrelevant or nonspecific outcomes ( n = 53), reviews or conference abstracts ( n = 15), short birth spacing ( n = 6), and overlapping population ( n = 4). With additional manual search, 129 studies comprising 46 874 843 participants were ultimately included in the systematic review (Figure S1), including 90 cohort studies, 11‐14,17‐19,34‐116 23 cross‐sectional studies, 10,117‐138 15 case–control studies, 8,139‐152 and 1 cluster‐randomized trial 153 . The baseline characteristics of the eligible studies are presented in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…It has been calculated that maternal mortality has been reduced globally by 30% by the increase in contraceptive use [4]. Unintended pregnancies, pregnancy spacing, and reducing high-risk pregnancies are the consequences of contraceptive use [5][6][7]. Current studies show that every year, contraceptive use could reduce nearly 230 million births by stopping unwanted pregnancies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies show that every year, contraceptive use could reduce nearly 230 million births by stopping unwanted pregnancies [8]. As a result, the use of contraception improves the health of women and their children [6,9]. However, the prevalence of contraceptive practice varied between 11.3% and 72.1% in different countries, namely Mozambique, 11.3%, Ghana, 21.5%, Bangladesh (modern method), 54.0%, and Sweden, 72.1% [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%